KEDUDUKAN DAN KEWENANGAN: BADAN NASIONAL PENGELOLA PERBATASAN DI INDONESIA - Widiartana, Putu Wahyu (UI Scholars Hub, 2021)
The vast condition of the Unitary Republic of Indonesia made Indonesia have several border areas stretching from Sabang to Merauke. Management of the countrys territories and border areas has been regulated in Law 43/2008 on State Territories. The National Border Management Agency (Badan Nasional Pengelola Perbatasan/BNPP) is the only institution tasked with managing border areas in Indonesia. The Minister of Home Affairs as the Head of BNPP leads and controls the implementation of the duties and functions of BNPP. In this study using Border Management Theory and Authority Theory. This research uses the normative legal research method which is the research conducted referring to the laws and regulations. The management of border areas in Indonesia still faces various problems, therefore the position and authority of the BNPP will be discussed briefly in this paper, along with comparisons in other countries.